Learning styles of Iranian EFL male high school seniors in computer-based and traditional face-to-face contexts - Moharrer, Zahra; Wong, Bee Eng (M. S. Thirumalai, 2013)
The Iranian education system has pursued the trend of using computers, especially at secondary school level, to help students cope with their learning problems independently. This study is an attempt to find out the different trends of learning style preferences among Iranian male high school seniors in two instructional formats, namely, computer-based and face-to-face learning. Willing's (1988) questionnaire was distributed among 236 students in the electronic distance education and traditional schools in Shiraz, Iran. The different types of language learners in this EFL context were investigated using Exploratory Factor Analysis. The findings indicated that learners in the computer-based context were largely not oriented adequately to learning English language through an interactive multimedia CD-ROM program independently. The findings also showed that although students in the traditional face-to-face context preferred the conventional classroom, they also showed communicative preference towards the opposite condition which is not prevalent in the Iranian traditional schools; in other words, they strongly preferred communication which was not highlighted in the school curriculum. Such findings have implications for the Iranian EFL classroom.